Left Ventricular End-Diastolic Dimension and Clinical Outcomes After Centrifugal Flow Left Ventricular Assist Device Implantation. Issue 2 (21st April 2021) - Truong, Vien T.; Shreenivas, Satya; Mazur, Wojciech; Egnaczyk, Gregory F.; Palmer, Cassady; Rao, Sriram D.; Rame, J. Eduardo; Chung, Eugene S.
Abstract : Supplemental Digital Content is available in the text. Abstract : The impact of preoperative end-diastolic left ventricular dimension (pre LVEDD) on long-term outcomes with centrifugal continuous-flow left ventricular assist device (CF-LVAD) is not well established. Accordingly, we performed an analysis of the Interagency Registry for Mechanically Assisted Circulatory Support (INTERMACS) registry to study this relationship. All patients with centrifugal CF-LVAD in the INTERMACS registry from June 2006 to December 2017 were screened. The final study group consisted of 3, 304 patients. After a median follow-up of 9.0 months (interquartile range [IQR], 4.2–18.8 months), 2, 596 (79%) patients were alive. After adjusting for significant covariates, increased pre LVEDD was associated with lower mortality (hazard ratio [HR], 0.91; 95% confidence interval [CI], 0.84–0.98; p = 0.01), stroke (HR, 0.85; 95% CI, 0.77–0.93; p < 0.001), and gastrointestinal bleeding (HR, 0.88; 95% CI, 0.80–0.97; p = 0.01), although there were more arrhythmias (HR, 1.14; 95% CI, 1.05–1.24; p = 0.003). Our study suggests that pre LVEDD is an independent predictor of mortality and adverse events in patients treated with centrifugal CF-LVAD. pre LVEDD should be considered an important preimplant variable for risk stratification when considering a CF-LVAD.